1963
DOI: 10.1029/jz068i009p02541
|View full text |Cite
|
Sign up to set email alerts
|

Some characteristic features of the equatorial ionosphere and the location of theF-region equator

Abstract: The characteristic features of the equatorial F region are studied using the published ionospheric data. The study reveals some important differences in the Asian, African, and American zones. In the diurnal variation of foF2 there are two peaks, one in the forenoon and the other in the afternoon, in the Asian zone, whereas the afternoon peak is absent in the American zone during sunspot maximum. The width of the equatorial trough is smaller in the American than in the Asian zone. The location of the F‐region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 9 publications
(6 reference statements)
1
12
0
Order By: Relevance
“…Its description was greatly advanced by the ionospheric sounders in place during the International Geophysical Year (IGY) of 1957-1958[Wright, 1962Rao, 1963]. Its significance as the highest F layer electron density on the planet has inspired numerous observational and theoretical studies [Kelley, 1989;Doherty et al, 1997], and its role as the locus of maximum scintillation on transionospheric RF propagation has further stimulated continued interest [Aarons, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…Its description was greatly advanced by the ionospheric sounders in place during the International Geophysical Year (IGY) of 1957-1958[Wright, 1962Rao, 1963]. Its significance as the highest F layer electron density on the planet has inspired numerous observational and theoretical studies [Kelley, 1989;Doherty et al, 1997], and its role as the locus of maximum scintillation on transionospheric RF propagation has further stimulated continued interest [Aarons, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of the F region in the equatorial and middle latitudes is well known. In the middle latitudes, the diurnal variation of LF•, the critical frequency for the F• region, shows a single smooth maximum in the afternoon; in the Asian equatorial region the diurnal variation shows two maximums, one in the forenoon and the other in the afternoon; in the American equatorial region the afternoon peak is absent during some years of the solar cycle but present in others [Rao, 1963]. In the transition region, extending from about 30.0 ø to 40.0 ø dip and lying between these two zones., the F region exhibits some characteristic features.…”
mentioning
confidence: 99%
“…It may be seen from the results presented here that the postsunset height rise in the equatorial regions has a seasonal and magnetic activity dependence exhibited by these two phenomena. It also has the same type of solar activity control [Rao, 1963]. It is, therefore, concluded that the postsunset height rise is the causative mechanism of spread F and flutter fading; other processes may sustain these phenomena over several hours, once they start.…”
Section: Model Of the Horizontal F-region Drift Pattern In Low Latitumentioning
confidence: 99%